Working for the State. Employment relations in the public services (Basingstoke, 2011)
"The last three decades have witnessed the almost continual reform and re-organisation of the UK's public sector and public services, with yet more reforms underway. The impact of these reforms on the experiences of the public sector's six million workers and those employed in the private sector but providing public services are examined in this book.